Ecthyma gangrenosum in a 3‐year‐old boy post‐heart transplantation. Issue 4 (30th June 2019) - Fukui, Kana Okazaki; Shoji, Kensuke; Nagai, Yusa; Shindo, Takahiro; Hikosaka, Makoto; Kuwahara, Kosuke; Ishiguro, Akira; Miyairi, Isao
Abstract: Ecthyma gangrenosum (EG) is a serious bacterial infection in immunocompromised patients. EG in transplant recipients is rarely reported and may go unrecognized, which may delay initiation of appropriate treatment. We report a case of EG in a pediatric heart transplant recipient who was treated successfully with antibiotics and surgical debridement.